Reimagining responsive approaches to curbing substance abuse by female students in Zimbabwe’s secondary schools - Wonder Muchabaiwa; Jigu Katsande; Annah Moyo (S&Co Publishing, 2025)
The rise of substance abuse among youths in Zimbabwe has reached disturbing levels, with female secondary school students increasingly falling victim. Historically, substance abuse was viewed as a male-dominated issue, with girls and women largely excluded from its narrative. This study, conducted in the Harare Metropolitan province, explores the factors contributing to female students' engagement in substance abuse and the subsequent impact on their educational experiences. Utilizing a qualitative research approach, the study employed grounded theory to collect, analyze, and present data on the issue. Participants were selected through purposive and snowball sampling techniques, with data gathered via focus group discussions with teachers and in-depth interviews with school administrators and affected students. This study highlights that substance abuse among female students is primarily driven by immediate environmental factors, particularly within the family unit. The prevalence of broken homes and parental absenteeism, often resulting from migration, increases young girls' vulnerability to substance abuse. It reveals a rise in substance abuse among female students, leading to serious implications for their academic performance and general schooling experiences. Key consequences include higher dropout rates and declining academic performance, triggering anti-school behaviors such as truancy, neglect of responsibilities, and violence. It also exposes them to mental health issues, vulnerability to sexual violence, exposure to STIs, and early pregnancies. In response, a concentric model is proposed to effectively address and curtail substance abuse among secondary school students.